(untitled) (Research, Society and Development, 2022)
The soil structure consists of pedogenic and biogenic aggregates, formed respectively by the hierarchy of aggregates and the action of macrofauna, especially earthworms. The behavior of these organisms in the soil is directly related to the management systems used in agroecosystems, as they are sensitive to the different managements adopted in agricultural areas. The objective was to compare chemical attributes of soil and coprolites of native earthworms in family production subsystems with agroecological and conventional production. The variables studied were analyzed using the statistical model, in a completely randomized design, with a factorial scheme (2x3x4), two management systems (conventional and agroecological), three collection depths (surface - coprolites, soil - 0 to 20 cm and 20 to 40 cm) and four agroecosystems (banana, vegetables, corn and cassava), totaling 24 treatments, with nine replications. There was a significant triple interaction effect on the chemical characteristics of earthworm coprolites and soil at depths of 0-20 cm and 20-40 cm, between production systems (S), depths (P) and subsystems (A) in all variables studied, except for Ca2+, SB and CTC, which had significant double interactions. The activity of earthworms in the soil reflects greater efficiency in the quality of the chemical attributes of the biogenic aggregates, expressed by the higher values of pH, organic matter, phosphorus, potassium and magnesium and lower values of aluminum and potential acidity. The conventional management system promotes higher levels of phosphorus, potassium and magnesium, however, higher levels of aluminum, sodium and potential acidity than the agroecological management system.